Earnings Quality: Impact of Income Smoothing, Earnings Persistence, Book Tax Difference with Good Corporate Governance as Moderation - Sormin, Feber; Aryati, Titik (International Journal of Emerging Trends in Social Sciences, 2021)
This study has a purpose to determine the effect of Income Smoothing, Earnings Persistence, Book Tax Difference on Earnings Quality and moderating effect of Good Corporate Governance. Using 98 sample data from manufacturing entities on the Indonesia Stock Exchange in 2015-2020, a negative effect of earnings persistence on earnings quality, and a positive effect of differential book tax on earnings quality found in this study, while income smoothing does not. In addition, it was found that good corporate governance by institutional ownership as a proxy strengthens the effect of income smoothing on earnings quality and weakens the effect of book-tax differences on earnings quality. This finding can be used by investors in assessing the quality of earnings from financial information issued by issuers so that future earnings prediction analysis can be measured properly so that the desired return target is achieved.